Study of morphological variations of liver in human - Haobam Rajajee Singh; Suganthy Rabi (Elsevier, 2019)
Introduction: Knowledge of variations in the external morphology of liver is essential during radiological investigations and surgery. There are only a few studies which have dealt with the surface variations of the liver. The aim of the present study is to determine the gross anatomical variations of the liver in the South Indian population. Material and methods: The morphological variations of the liver such as changes in size and shape, presence of fissures, pons hepatis and accessory lobes were noted in 70 formalin fixed livers. Results: The morphological variations included fissures in the right, left, caudate and quadrate lobes of the liver (81.4%), elongated left lobe or Beaver's lobe or Netter's type 4 (12.86%), Netter type 2 liver (1.43%), pons hepatis (22.9%), conical shaped right lobe (18.57%), notched border (10%), accessory lobe (12.86%) and quadrate lobe with tongue like projection (7.14%). Variations in caudate lobe including underdeveloped and hypertrophied caudate and papillary process were noted. Conclusion: In this study, various morphological variations of liver were observed. The awareness about this will aid the radiologists to make more accurate analysis of the radiological images and thereby aiding in the reduction of the false reports. Keywords: Fissure, Beaver's lobe, Pon hepatis, Accessory lobe, Caudate lobe